APPLICATION OF DATA MINING IN INFORMATION CONCERNING PATIENT RECORDS - Carvalho, Ricardo César de (Informação em Pauta, 2018)
This article seeks to investigate the application of Data Mining in the discovery of knowledge derived from information from patient records. Therefore, the objective was to examine the bibliography in the search of the use, results and investments in the area. The methodology used consisted of a literature review, through literature review and the application of a step of data mining, the importation into health data. It is concluded that Data Mining is efficient, there are already a lot of researches and investments of large companies and now, it has a great growth potential.